Pedestrian perception towards signalized crossing - Ahmad Farhan, Ahmad Nazri (2016)
Walking involve interaction between the local environment in a way that is not possible through motor transport. Good, well maintained and safe pedestrian facilities that are comfortable to be used by the pedestrians could encourage people to travel by walking. Different travel purpose usually influences the pedestrian perception towards the existing pedestrian facilities. This paper presents the findings of pedestrian perception towards signalized crosswalk. A questionnaire survey was carried out in order to assess the pedestrian travel purpose and pedestrians' perception of the signalized crosswalk. The survey also investigated pedestrian perceptions of safety, level of understanding, behaviour and other factors that influence levels of compliance at signalized crosswalk. A mix land-use area within the city of Kuantan that consists of shopping mall, public transport service, business centre and education centre were chosen as the study area. This study found that safety of the crossing is the most important factor to pedestrian regardless of their travel purpose. Whereas, aesthetic and amenities are important factor for pedestrians that used the crossing for shopping or leisure purposes and transit commuters. In conclusion, most of the pedestrian satisfied with the existing crossing facilities condition but in different aspect based on the pedestrian‟s purposes.